Phonological Transformation Of Fusha To ‘Ammiyah Egypt: Case Study On Sabry Aleel Song : At-Tahawwul aṣ-Ṣawtī min al-Fuṣḥā ilā al-‘Āmmiyyah al-Miṣriyyah: Dirāsah Ḥālah ‘alā Ughniyat Ṣabry Aleel - Ulinnuha, Nur Atika Rima; Tulus Musthofa; Mhd. Rizalman (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2025)
This article examines the phonological change from Fusha Arabic to Egyptian dialect ('Ammiyah) in the context of the song